(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND Acid base and electrolyte disorders are frequently reported in the early period after renal transplantation. No comprehensive data exist on the prevalence and patterns of, and contributing factors to, electrolyte disturbances in patients with stable long-term allograft function. METHODS We analysed 576 renal transplant recipients (serum creatinine level <2.0 mg/dl) in a cross-sectional study to evaluate the prevalence of electrolyte disorders and the risk factors associated with their occurrence. RESULTS A total of 369 patients (64%) of all allograft recipients (n = 576) showed at least one electrolyte and acid base disorder. The most abundant disorder was hypomagnesaemia (25%, n = 143), followed by hyperkalaemia (12.8%, n = 74), hypercalcaemia (12%, n = 69), hypophosphataemia (11.6%, n = 67), metabolic acidosis (11.1%, n = 61) and hyponatraemia (9%, n = 52). All other electrolyte disorders were rare (<6%). In most cases the electrolyte disorders could be classified as mild. Forty percent of the cases had a combined disorder, but without a preferential pattern of combinations. In a multivariate logistic regression analysis, the most important factors contributing significantly to the occurrence of electrolyte disorders were renal function and concomitant medications. CONCLUSION Acid base and electrolyte disorders are frequently observed in stable renal allograft recipients, but are usually mild. A combination of two or more electrolyte abnormalities often occurs, although no predominant pattern of a unique combination of electrolyte disorder is recognizable.